CFD modeling of fly-ash slurry to analyse the concentration and velocity profiles. (2020) - Kumar, Navneet; Kaushal, D.R.; Dwivedi, V.K.; Singh, Desh Bandhu; Sharma, S.K.; Yadav, J.K.
Abstract: Computational fluid dynamics simulations were performed for fly ash slurry of 21 μm in a 50 mm pipeline with efflux concentrations of 32.52, 36.55 and 41.53 percent (by volume) at 1 and 1.5 m/s flow velocities to calculate concentration and velocity profiles. In this analysis, the Eulerian two-phase model was used in Ansys Fluent software for simulations. Concentration and velocity profiles to consider the transport mechanism of solid–liquid flow in the slurry mode were predicted and analyzed vis-à-vis observed flow characteristics.